2022
DOI: 10.3389/fenvs.2022.971204
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the PM2.5 aerosol fraction monitored at a suburban site in south-eastern Italy by integrating isotopic techniques and ion beam analysis

Abstract: Both teflon and quartz PM2.5 filters collected from January to July 2021 at the monitoring site of the Department of Mathematics and Physics of the University of Salento in Lecce (Italy) were analyzed by integrating different characterization techniques (Particle Induced X-ray Emission PIXE, Isotope Ratio Mass Spectrometry IRMS, and Accelerator Mass Spectrometry AMS) at the CEDAD (Center of Applied Physics, Dating and Diagnostics) of the Department of Mathematics and Physics, University of Salento. The PM2.5 c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 44 publications
0
1
0
Order By: Relevance
“…Previous studies 14 have shown that low-cost sensor measurements more closely match reference monitors at locations with low traffic than at high traffic locations. 49 To understand the underlying differences between two data sets and identify any drivers of PA data inaccuracy, a frequency-based analysis proves to be helpful. As aerosol sources have distinct time-period signatures, frequency analysis can help determine the relative response of PA sensors to different emission sources.…”
Section: Monitoring Data Summarymentioning
confidence: 99%
“…Previous studies 14 have shown that low-cost sensor measurements more closely match reference monitors at locations with low traffic than at high traffic locations. 49 To understand the underlying differences between two data sets and identify any drivers of PA data inaccuracy, a frequency-based analysis proves to be helpful. As aerosol sources have distinct time-period signatures, frequency analysis can help determine the relative response of PA sensors to different emission sources.…”
Section: Monitoring Data Summarymentioning
confidence: 99%